2015
DOI: 10.3892/or.2015.4055
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin causes inactivation and degradation of the androgen receptor by inducing the restoration of miR-449a in prostate cancer

Abstract: Capsaicin, a novel antitumor agent extracted from chili peppers, has been proven to induce growth inhibition in various types of cancer including prostate cancer. However, the detailed mechanisms remain largely undiscovered. In the present study, we explored the regulation of the androgen receptor (AR) by capsaicin and further researched the mechanisms of their interaction in AR-positive prostate cancer cells. In the present study, cell viability was assessed by MTT assay. Cell cycle distribution was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Capsaicin exhibits antiproliferative actions on prostate cancer cells by inducing apoptosis. It reduces the expression of the androgenic receptor, inhibits the activity of the proteasome which suppresses the degradation of inhibitor of nuclear factor kappa B (IĸBα), thereby preventing the activation of NF-ĸB (152). Such actions might play a role in the treatment of prostate cancer, even hormone-independent.…”
Section: Indole 3 Carbinol (I3c) Di-indoylmethane (Dim) Andmentioning
confidence: 99%
“…Capsaicin exhibits antiproliferative actions on prostate cancer cells by inducing apoptosis. It reduces the expression of the androgenic receptor, inhibits the activity of the proteasome which suppresses the degradation of inhibitor of nuclear factor kappa B (IĸBα), thereby preventing the activation of NF-ĸB (152). Such actions might play a role in the treatment of prostate cancer, even hormone-independent.…”
Section: Indole 3 Carbinol (I3c) Di-indoylmethane (Dim) Andmentioning
confidence: 99%
“…Capsaicin caused micro-RNA-mediated modulation of cell survival pathways: Recent studies have demonstrated that capsaicin can modulate the expression of certain microRNAs (miR), thereby inducing apoptosis in pancreatic, prostate, and liver cancer cells. Incubation of human prostate cancer cells with capsaicin reduced androgen receptor (AR)-mediated signaling via induction of miR-449a (98). Capsaicin diminished the expression of microRNA miR-520a-5p, and combined treatment with miR-520a-5p inhibitor with capsaicin showed more potent anti-proliferative effects in K562 leukemic cells compared with capsaicin treatment alone (99).…”
Section: Role Of Capsaicin In Regulating Tumor Cell Proliferationmentioning
confidence: 99%
“…Recently, capsaicin has been evaluated for anti-carcinogenic properties. Capsaicin effects on prostate cancer using the transgenic adenocarcinoma of the mouse prostate (TRAMP) model was found to be chemopreventive [6], whereas it was also found to decrease prostate cancer cell proliferation and cell cycle progression through the inactivation of androgen receptor [7]. It was also found to modulate extracellular matrix components in an experimentally induced lung cancer model, suggesting it could also have an anti-tumor effect in lung cancer as well [8].…”
Section: Introductionmentioning
confidence: 98%